2005
DOI: 10.1093/ajcn/81.5.1198
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient deficiencies and gender: social and economic costs

Abstract: Vitamin and mineral deficiencies adversely affect a third of the world's people. Consequently, a series of global goals and a serious amount of donor and national resources have been directed at such micronutrient deficiencies. Drawing on the extensive experience of the authors in a variety of institutional settings, the article used a computer search of the published scientific literature of the topic, supplemented by reports and published and unpublished work from the various agencies. In examining the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
121
2
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(130 citation statements)
references
References 24 publications
3
121
2
4
Order By: Relevance
“…Despite major concerted international efforts, eradication of MNM has remained a widespread and persistent global health problem in developing countries, where it continues to exact an enormous toll on individuals, populations, and society [7]. Food-based approachesdesigned to increase micronutrient intake through the diet -represent the most desirable and sustainable method of preventing MNM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite major concerted international efforts, eradication of MNM has remained a widespread and persistent global health problem in developing countries, where it continues to exact an enormous toll on individuals, populations, and society [7]. Food-based approachesdesigned to increase micronutrient intake through the diet -represent the most desirable and sustainable method of preventing MNM.…”
Section: Discussionmentioning
confidence: 99%
“…Micronutrient supply is among the main preventive and curative interventions with proven and substantial capability to contribute towards achieving these goals [12]. Widespread MNM also results in an enormous negative socio-economic impact at the individual, community, and national levels [7].…”
Section: Micronutrient Malnutrition Todaymentioning
confidence: 99%
“…The positive association between maternal education and health and nutritional status of children is well established 32,33 . Educated women have fewer children, seek medical attention sooner for themselves and their children, and provide better care and nutrition for their children 34 .…”
Section: Inadequate Investmentmentioning
confidence: 99%
“…Similar economic gains can be achieved by preventing low birth weight children, reproductive failure and child mortality [69]. Another study, in Ecuador, found that people with moderate ID were paid less for agricultural work (Greene, 1977. cited in [70]. More recently, the WHO study groups looked at the cost-effectiveness and benefit-to-cost ratios of micronutrient interventions, nutrient fortification and salt iodization programs; both study groups established very high benefit-to-cost ratios [68,71].…”
Section: Iodine Deficiency and Community Capacity Buildingmentioning
confidence: 99%